Improvement of cold flow properties of Cocos nucifera and Calophyllum inophyllum biodiesel blends using polymethyl acrylate additive - Islam, M.M.; Masjuki, Haji Hassan; Kalam, Md. Abul; Zulkifli, Nurin Wahidah Mohd; Habibullah, M.; Hossain, M.M. (Elsevier, 2016)
Biodiesel, which comprises of fatty acid esters, is an alternative fuel for diesel engines. However, biodiesel has poorer cold flow properties (CFPs; i.e., cloud point (CP), cold filter plugging point (CFPP), and pour point (PP)) than diesel fuel. This study aims to reduce the PP, CFPP, and CP of two different biodiesels, namely, Cocos nucifera (coconut) and Calophyllum inophyllum (C. inophyllum), using polymethyl acrylate (PMA) additives. This study also investigates the effect of PMA on other biodiesel properties. Various physicochemical properties were measured and compared with the ASTM D6751 and EN14214 standards. Differential scanning calorimetry was used to observe the crystal behavior of the biodiesel blends. Results showed that 20% of biodiesel blended with diesel (B20) and 0.03 wt% of PMA showed the highest improvement in the CP, PP, and CFPP. This study also investigates the influence of PMA on oxidation stability, flash point, heating value, and kinematic viscosity. These properties of B20 satisfy the ASTM D6751 and EN14214 standards. The process of crystal aggrandizement and the rate of wax crystal precipitation of B20 can be modified by PMA, resulting in enhanced CFPs of the biodiesel blend. Therefore, PMA is an effective cold-flow-improving additive for coconut-based and C. inophyllum-based biodiesel blends. Moreover, the results indicated that 20% coconut and C. inophyllum biodiesel blends with 0.03 wt% of PMA can be used in cold climate areas without any problem in terms of fuel physicochemical quality.